Learning Tableau 10.x - Acharya, Govind (Packt, 2018)
"In this course, you'll be introduced to Tableau and understand the different versions of the software including Tableau Desktop, Tableau Desktop Professional, Tableau Public, Tableau Online, and Tableau Server. The course contains session material that covers both fundamental and advanced concepts to create worksheets, dashboards, and stories in Tableau. You'll get a solid understanding of the user interface and all the powerful functions available in Tableau. Furthermore, you'll learn about other topics such as table calculations, parameters, filters, user-defined calculations, (variables). Next, you'll see how to use dashboard actions to create interactivity between dashboard components and how to "drill-down" into more dashboards containing additional detail for specific data elements. By the end of the course, you'll be adept with the knowledge to create great visualizations with Tableau for your day-to-day business needs."--Resource description page